Manajemen Produksi Pada Perkebunan Kelapa Sawit PT. Lkk Kabupaten Pali - Siswanti, Ayu; Azmi, Nur; Umikalsum, R.A (Jurnal Multidisiplin Dehasen (MUDE), 2025)
PT. Laras Karya Kahuripan (LKK) is a company engaged in the agricultural sector, namely oil palm, located in Karang Tanding Village, Pali Regency. With a fairly large number of employees, namely 455 people. PT. LKK was first established in 2004. PT. LKK is one of the companies that contributes to producing oil palm in South Sumatra. The area of ​​PT. LKK reaches 3,765.53 ha. This study aims to determine and analyze the production management, problems of oil palm plantations of PT. LKK, Pali Regency. The research method used is a case study with a purposive data collection technique. The results of the study show that production management at PT. Laras Karya Kahuripan (LKK) Pali Regency include production aspects, namely production planning, land preparation and land area, seed selection, planting, care and maintenance, harvesting and production planning, clear and effective organizational structure, bookkeeping and reporting. Human resource aspects, namely employees and their duties. The marketing aspect at PT. LKK is conducting direct sales to PT. GBS. The environmental management aspect at PT. LKK already has official legality in the form of a certificate. The problems faced by PT. Laras Karya Kahuripan (LKK) related to ISPO are not fully implementing Good Agricultural Practice (GAP) standards, certification costs, community conflicts and labor allocation.